Pengembangan dan Efektivitas Video Animasi Berbasis Multimedia Dalam Meningkatkan Hasil Belajar IPAS Siswa Kelas III Sekolah Dasar - Kadek Pina Destrya Lestari; I Made Sedana; I Made Ariasa Giri (Jayapangus Press, 2026)
The low learning outcomes of third-grade elementary school students in Natural and Social Sciences (IPAS) indicate the need for learning media that can present abstract concepts in a more concrete and engaging way. This study aimed to develop and analyze the effectiveness of multimedia-based animated videos in improving IPAS learning outcomes among third-grade elementary school students. This research employed a Research and Development (R&D) method using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. The subjects consisted of 43 third-grade students in Gugus II Kecamatan Seririt, divided into an experimental class of 16 students and a control class of 27 students, along with four teachers involved in the practicality test. The instruments used were expert validation sheets, teacher and student response questionnaires, and IPAS learning outcome tests in the form of pretest and posttest. The results showed that the developed animated video was highly valid, with validity scores of 0.94 from media experts, 0.96 from material experts, and 0.94 from language experts. The practicality test showed that the media was highly practical, with a teacher response score of 96.67% and a student response score of 88.25%. The effectiveness test showed that the experimental class obtained a higher posttest mean score of 85.63 than the control class, which obtained 71.48. The independent sample t-test produced t = 8.72, df = 41, and p < 0.001, indicating a significant difference in learning outcomes. The N-Gain score of the experimental class was 0.68, while the control class obtained 0.37. Therefore, multimedia-based animated videos are valid, practical, and effective for improving IPAS learning outcomes among third-grade elementary school students.